KEANEKARAGAMAN JENIS MANGROVE DI DESA MENDALOK KECAMATAN SUNGAI KUNYIT KABUPATEN MEMPAWAH - Muharamsyah, Syahrul; Anwari, M Sofwan; Ardian, Hafiz (Universitas Tanjungpura, 2019)
Mangrove forests are unique ecosystems that have ecological, biological and socio-economic functions. The function of mangrove forests on the environment is very important especially in the coastal and oceanic regions. Mangrove forests providers of wood, leaves as raw material for medicines, and natural dye. This study aims to inventory the diversity of species of mangrove vegetation in Mendalok Village, Sungai Kunyit Subdistrict, Mempawah Regency. The benefits of this study are to provide the data on mangrove forest vegetation as basic data for local government and related agencies in efforts to protect and preserve mangrove forests in Mendalok Village, Sungai Kunyit Subdistrict, Mempawah Regency. Inventory the tree in mangrove forest used a line with measured 200 meters. There are 6 lines and the distance between the lines as far as 100 meters. The lines of observation are placed by purposive sampling. The results of research found 11 types of species and consisted of 6 genera. The genera are Avicennia, Bruguiera, Ceriops, Rhizophora, Soneratia and Xylocarpus. The species found were Avicennia alba, Avicennia marina, Bruguiera cylindrica, Bruguiera gymnorrhiza, Bruguiera parviflora, Ceriops decandra, Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa, Sonneratia caseolaris, Xylocarpus mollucensis. Diversity of mangrove species in Mendalok Village, Sungai Kunyit Subdistrict, Mempawah Regency was high and should be maintained for conservation and ecotourism area. Keywords : conservation, ecotourism, mangrove, Mendalok Village